NON-TRAUMATIC SUBARACHNOID HEMORRHAGE IN A 57-YEAR-OLD WOMAN WITH A LONG HISTORY OF VERTIGO: CASE REPORT - Putri, Berlian Ristina; Satiadarma, Tiffany; Mawaddah, Syarifiyana; Indriyono, Andhy (Journal of Pain, Headache and Vertigo, 2025)
Background: Indonesia has a high burden of stroke, became the number one cause of death. Among countries in Asia, Indonesia has the highest stroke mortality rate. Ischemic stroke, intracerebral hemorrhage, and subarachnoid hemorrhage were sequentially the highest to lowest prevalence of stroke. Subarachnoid hemorrhage most often causes severe headaches which patients may describe as the worst headache of their life, accompanied by vomiting and stiff neck. Focal neurological deficits to coma can appear depending on the severity of the disease. Vertigo is an alarming symptom that could indicate the existence of an unruptured intracranial aneurysms that predominantly causes non traumatic subarachnoid hemorrhage. Case: A 57-year-old woman came to the emergency room with decreased consciousness GCS E3V1M4 after falling in the bathroom 30 minutes before admission. Accompanying complaints were projectile vomiting. The patient had a history of chronic vertigo. History of hypertension, diabetes and smoking were denied. From physical examination neck stiffness, positive Brudzinski I, and right laterality were found. Non-contrast head CT scan findings showed subarachnoid and intraventricular hemorrhage. Leukocytosis (16,300/μL) and hypokalemia (2.8 mmol/L) were found in laboratory examinations. Mannitol, citicoline, acetazolamide, nimodipine, ketorolac, ondansetron, and ranitidine were given. The patient experienced clinical improvement after 18 hours of treatment in the ICU with GCS increase to E3V5M6. After 15 days of hospitalization, the patient experienced significant clinical improvement. Conclusion: Recognition of risk factors, early diagnosis, and management of subarachnoid hemorrhage are important in preventing morbidity and mortality and improving patient outcomes.